Caracterización fenotípica del Bovino Criollo (bos primigenius taurus) en la Provincia de Cotopaxi. - Sanchez Montesdeoca, Dario Fernando (2018)
The investigation was carried out in the province of Cotopaxi Latacunga, Pujilí, Salcedo, and Saquisili Cantons, with the objective of determining the phenotypic characters of the Creole bovine (Bos primigenius taurus) beginning with a geographical mapping, surveys and data collection of zoometric measurements at a number of Creole bovine animals identified according to a sample; later it was established that in Latacunga and Pujilí Cantons there is a percentage of 24.67% of animals, in relation to Salcedo Canton, which has 25.84%; and Saquisili 24.82% of a total of 3316 animals by using a multivariate analysis allowed the researcher to correlate each of the variables under study that depend on each of the localities allowing to define if there are significant differences between each of the medians. For the variable Liters / milk / day, it can be stated that there is an average of 565,473 liters / milk / day. With a coefficient of variation of 98.09%, presenting average values of 6 liters / milk / day, and maximum values of 13 liters / milk / day, concluding.